The Influence Of Online Learning On The Interest In Learning 5th Grade Students Of SD Negeri Mattoangin II Mariso District, Makassar City - Nur Abidah Idrus (Program Studi PGSD FIP UNM, 2022)
This research is a survey research that examines the influence of online learning on students' learning interests. The purpose of this study is (1) to determine the implementation of online learning for grade V students of SD Negeri Mattoangin II, Mariso District, Makassar City (2) to find out the interest in learning for grade V students of SD Negeri Mattoangin II, Mariso District, Makassar City (3) to find out the influence of online learning on the interest in learning of grade V students of SD Negeri Mattoangin II, Mariso District, Makassar City. This research approach is quantitative research using descriptive analysis. The population of this study was all students of class V. The sample in this study was class V with a total of 60 students. With sampling technique using Total Sampling. Data collection techniques in this study use questionnaires, interviews and documentation. The results showed low interest in student learning at the time of online learning. This is evidenced by a survey of learning interests that obtained percentage results This is evidenced by a survey of learning interest which obtained the results of a percentage of 29% who felt it was appropriate to do online learning and another 71% felt inappropriate. Based on the results of this study, it can be concluded that online learning causes low interest in learning for grade V students of SD Negeri Mattoangin II, Mariso District, Makassar City.